INFLUENCE ONLINE CUSTOMER REVIEWS AND QUALITY INFORMATION OF PURCHASE DECISIONS AT SHOPEE YASASHI JAPAN SHOP - Rudi Hermawan (Cita Konsultindo Research Center, 2023)
This study aims to determine the effect of online customer reviews and information quality on purchasing decisions at Shopee Yasashi Japan Shop. The research method was used a quantitative method. The population in this study are the Shopee Yasashi Japan Shop consumers. Sampling was done using probability sampling technique with random sampling method. The sample in this study consisted of 98 respondents that had bought products at Shopee Yasashi Japan Shop. Collecting data was using a questionnaire. The collected data was scored and then analyzed using the SPSS (Statical Program for Social Science) 23.0 for Windows program.The results of this study indicate that Online Customer Review (X1) has a positive and significant influence on Purchase Decisions (Y) at Shopee Yasashi Japan Shop by 68%. Information Quality (X2) has a positive and significant influence on Purchase Decision (Y) at Shopee Yasashi Japan Shop by 51.4%. Online Customer Review (X1) and Information Quality (X2) have a positive and significant influence on Purchase Decision (Y) at Shopee Yasashi Japan Shop simultaneously on variable Y amounting to 84.5% and 15.5% influenced by other variables that not investigated by researchers in this study.